Impact of CT photon-counting virtual monoenergetic imaging on visualization of abdominal arterial vessels - Dillinger, Daniel; Overhoff, Daniel; Booz, Christian; Kaatsch, Hanns L.; Piechotka, Joel; Hagen, Achim; Froelich, Matthias F.; Vogl, Thomas J.; Waldeck, Stephan (Diagnostics, 2023)
Purpose: The novel photon-counting detector (PCD) technique acquires spectral data for virtual monoenergetic imaging (VMI) in every examination. The aim of this study was the evaluation of the impact of VMI of abdominal arterial vessels on quantitative and qualitative subjective image parameters. Methods: A total of 20 patients that underwent an arterial phase computed tomography (CT) scan of the abdomen with a novel PCD CT (Siemens NAEOTOM alpha) were analyzed regarding attenuation at different energy levels in virtual monoenergetic imaging. Contrast-to-noise ratio (CNR) and signal-to-noise ratio (SNR) were calculated and compared between the different virtual monoenergetic (VME) levels with correlation to vessel diameter. In addition, subjective image parameters (overall subjective image quality, subjective image noise and vessel contrast) were evaluated. Results: Our research showed decreasing attenuation levels with increasing energy levels in virtual monoenergetic imaging regardless of vessel diameter. CNR showed best overall results at 60 keV, and SNR at 70 keV with no significant difference to 60 keV (p = 0.294). Subjective image quality was rated best at 70 keV for overall image quality, vessel contrast and noise. Conclusions: Our data suggest that VMI at 60-70 keV provides the best objective and subjective image quality concerning vessel contrast irrespective of vessel size.
Gesehen am 18.07.2024